Produksi gula pereduksi dari kulit kopi robusta dengan metode hidrolisis asam - Danu Indra Wardhana; Ahib Assadam; Ara Nugrahayu Nalawati; Retno Murwanti (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
The high productivity of coffee in Indonesia resulted in abundant coffee husk. Unfortunately, the coffee husk has not been utilized optimally. This research aimed to determine the effect of variations and acid concentration. Two-stages acidic hydrolysis process using two kinds of different chemical reagents i.e sulfuric acid (H2SO4) and hydrochloric acid (HCl) with the variation of concentration such as 10 %, 20 %, and 30 % with temperature of 30 0C and 75 0C for five hours in water bath shaker with the rate agitation 120 rpm. The hydrolysates produced neutralized using NaOH 2N, so that the process of hydrolysis easily. The result showed that in acidic hydrolysis process of coffee husk the reactant HCl generates levels of reducing sugar higher than the reactant H2SO4. In addition, the best treatment was hydrolysis by using reagent HCl 30 % with the levels total sugar, reducing sugar and degree of polymerization are of 20.85 %, 17.28 %, and 1.21.